2005
DOI: 10.1248/bpb.28.1852
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Morus alba on Compound 48/80-Induced Anaphylactic Reactions and Anti-Chicken Gamma Globulin IgE- Mediated Mast Cell Activation

Abstract: Mast cells are widely distributed throughout vascularized tissues and certain epithelia.1) Mast cells are responsible for a variety of allergic disorders including allergic rhinitis, dermatitis, asthma, and food allergies, as well as catastrophic anaphylactic reactions to insect stings and some drugs. These cells respond to IgE-directed antigens via the high-affinity receptor for IgE, Fce RI, by releasing granules that contain preformed inflammatory mediators and generating inflammatory lipids and cytokines. 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…26) Compound 48/80 stimulation of mast cells leads to the release of chemical mediators and causes an increase in vascular permeability at the stimulated site. 27,28) In this present clinical study, the oral administration of HWE did not affect the total and JCP-specific IgE concentrations in the serum. In our previous study using OVA-sensitized mice, 4 weeks continuous oral administration of HWE did not affect the total and OVAspecific IgE concentrations in the serum.…”
Section: Discussionsupporting
confidence: 40%
“…26) Compound 48/80 stimulation of mast cells leads to the release of chemical mediators and causes an increase in vascular permeability at the stimulated site. 27,28) In this present clinical study, the oral administration of HWE did not affect the total and JCP-specific IgE concentrations in the serum. In our previous study using OVA-sensitized mice, 4 weeks continuous oral administration of HWE did not affect the total and OVAspecific IgE concentrations in the serum.…”
Section: Discussionsupporting
confidence: 40%
“…Only a fraction of ~250,000 plant species have been studied for antiasthmatic activity till now. [14][15][16][17][18][19][20][21] WHO has reported that 80% people of world population believe in traditional medicine for their health management. 22 In our laboratory, we have screened a vast number of natural extract in the form of steam volatile oil in vitro for their inhibitory effect on mast cell degranulation and anaphylactic shock.…”
Section: Introductionmentioning
confidence: 99%
“…75 tBHP is also a ROS-producing agent that causes lipid peroxidation 76 [6]. High levels of ROS anti-hypertensive [12], anti-hyperglycemic [13], anti-microbial 98 [14], anti-allergic [15], anti-inflammatory [16], and neuroprotec-99 tive effects [17,18]. Among similar naturally occurring antioxidant 100 analogues, OXY is well known as a strong scavenger of free radicals 101 [19].…”
mentioning
confidence: 99%